Simulation of Vacuum Arc Characteristics at Different Moments Under Power-Frequency Current - 王立军 杨鼎革 贾申利 王流火 史宗谦 (Plasma science & technology, 2012)
In this paper, based on the quasi-stationary magneto-hydrodynamic （MHD） model, vacuum arc characteristics are simulated and analyzed at different moments under power-frequency current. For a vacuum arc with sinusoidal current under a uniform axial magnetic field （AMF）, simulation results show that at the moment of peak value current, maximal values appear in the ion number density, axial current density, heat flux density, electron temperature, plasma pressure and azimuthal magnetic field. At the same time, the distributions of these parameters along the radial position are mostly nonuniform as compared with those at other moments. In the first 1/4 cycle, the ion number density, axial current density and plasma pressure increase with time, but the growth rate decreases with time. Simulation results are partially compared with experimental results published in other papers. Simulations and light intensity near the cathode side is stronger than arcs. experimental results both show that the arc that near the anode side for diffusing vacuum